2014
DOI: 10.1002/j.2168-0159.2014.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

59.2: The Contributions of Built‐in Light on the Readability in E‐paper Devices

Abstract: In recent years, e-readers have spread to many countries. Most of e-readers have a reflective type of display called e-paper. The general view is that under conditions of low illuminance, readability of the e-paper display is poor. However, most recent e-readers have a built-in light system. This system would improve the readability of the e-paper display under low illuminance conditions. We carried out experiments to evaluate the readability e-paper devices using different systems. In the experiments, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…With regard to the evaluations by devices, as with our previous studies 1) 2) , in this study we found that the changes in the readability of reflective e-paper under various illuminance conditions were similar to those for paper text, and this tendency was remarkable in the older groups. The backlit LCD has its own light source and has a high resolution and contrast ratio, and no significant differences in reading were seen at any of the levels of illuminance.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With regard to the evaluations by devices, as with our previous studies 1) 2) , in this study we found that the changes in the readability of reflective e-paper under various illuminance conditions were similar to those for paper text, and this tendency was remarkable in the older groups. The backlit LCD has its own light source and has a high resolution and contrast ratio, and no significant differences in reading were seen at any of the levels of illuminance.…”
Section: Discussionsupporting
confidence: 85%
“…No significant differences were observed among the illuminance levels with the iPad, but the evaluations of the iPad were worse than Paper at the illuminance of 3,000 lx. These results were Table 2-1 Subjects' evaluations using four devices under six ambient illuminance levels similar to those that we obtained in a previous study 2) . Paper.…”
Section: Task Designsupporting
confidence: 87%
“…Much of the literature indicates that under conditions of high illuminance, readability of the self-illuminating display (LCD) is poor because of glare, particularly in outdoor sunlight. 29,30 On the contrary, readability of a reflective display (EPD) appears to perform closer to paper text when read under similar conditions. The introduction of the integrated lighting unit (ILU-EPD) in 2007 represented a form a hybrid between the previous two display technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of display contrast, color, and readability are necessary to evaluate displays for optimization of their performance. Subjective tests have compared the readability of reflective EPD without and with front light to that of tablet‐sized LCD with backlight in controlled lighting conditions . However, designers and manufacturers of mobile displays seek to predict ambient display performance for specific illumination environments from objective display measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective tests have compared the readability of reflective EPD without and with front light to that of tablet-sized LCD with backlight in controlled lighting conditions. 5 However, designers and manufacturers of mobile displays seek to predict ambient display performance for specific illumination environments from objective display measurements. Optical measurements for emissive displays were developed long before viable EPD.…”
Section: Introductionmentioning
confidence: 99%